Komunikasi Terapeutik Perawat dengan Tingkat Kecemasan Pasien Pre-Operasi di Ruang Instalasi Bedah Sentral RSUD Saras Husada Purworejo - Warsini Warsini; Winda Irwanti; R. Agus Siswanto (Alma Ata University Press, 2015)
The symptoms of anxiety relate to medical condition are often found, though there are various incidences for each condition. The surgery is a potential threat that may rise stress reaction either physically or psychologically. One factor that may decrease the level of anxiety of patients is nursing therpeutic communication. The purposes of this study were to know the relationship between nursing therapeutic communication and anxiety level of preoperative patients in central surgical instalation room at RSUD Saras Husada Purworejo. This study was used an observational with a cross sectional design. The population in this study was preoperative patients in central surgical instalation room at RSUD Saras Husada Purworejo. Samples were obtained by accidental sampling technique, which consisted of 81 respondent. Data analysis was done by Kendal Tau test. The results showed that nursing therapeutic communication was 37.0% in a good category. Anxiety level of preoperative patients was 44.4% in average level. The result of Kendall Tau test showed a p-value=0.000 (p<0.05). There was a relationship between nursing therapeutic communication and anxiety level of preoperative patients. In conclusion, there was a relationship between nursing therapeutic communication and anxiety level of preoperative patients in central surgical instalation room at RSUD Saras Husada Purworejo.